PREVALENCE OF WORK-RELATED MUSCULOSKELETAL DISORDERS AMONG IRANIAN ORTHOTISTS AND PROSTHETISTS: A STUDY ON WORK-RELATED QUALITY OF LIFE - Sarina Azizi; Vahideh Moradi; Behnam Hajiaghaei; Taher Babaee (Canadian Prosthetics & Orthotics Journal)
BACKGROUND: Work-related musculoskeletal injuries are prevalent globally and can impact both work efficiency and the quality of services offered to patients.